Investigating the Spatial planning components in Social science books Geographic chapters of the fourth and fifth grades - Karamali, Akram; Qorban, Fatemeh; Zohorian, Masumeh (International Review of Management and Marketing, 2017)
The present paper is driven from a study with the same title which has been conducted during the 2013 – 2014 academic year. This study aimed in investigating the content of the geographic chapters of social sciences’ books in fourth and fifth grades, based on their compliance with components of natural resources, managerial strategies, cultural factors and social justice. The statistical population of the study were the total number of 5700 elementary schools’ teachers of fourth and fifth grades in Tehran during 2013 – 2014 academic year. However, regarding the large statistical population, the sample size was determined using Krejcie and Morgan Table and 360 teachers were chosen from the study population and among all of the school districts of Tehran (north, south, east, west and center) through the multistage random cluster sampling method. The required data collected through a questionnaire which was developed by the researchers and confirmed by experts and professors with high validity and contain 24 subcomponents. Moreover, the reliability of the questionnaire was highly reported using Cronbach’s alpha coefficients of 0.896. The analytical results indicated that from the fourth and fifth grades teachers, spatial planning components have not been properly and thoroughly considered in the Geography Books. Among the studied components, more attention has been toward the natural resources and less attention toward social justice. They also believed that components such as natural resources, managerial factors, cultural factors and social justice have been neglected in Geography books. Keywords: Spatial Planning; Social Sciences School books. JEL Classifications: I2, A2, A3